Adoption of Improved Rice Processing Technologies: A case of Small-scale Processor Groups under IFAD-Value Chain Development Program in Niger State, Nigeria - Abubakar, H. N.; Umar, B. F.; Gbanguba, A. U.; Dauda, N. S.; Garba, Y.; Hamisu, S.; Abubakar, M. B. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
The study assessed the adoption of improved rice processing technologies focused on small-scale rice processors groups under IFAD- Value chain development program in Niger State. A multi-stage sampling procedure was used for selection of 160 rice processors. Data were generated using structured questionnaire. The study used descriptive and inferential statistics analysis of the data. The results described that 52% of the respondent were between the age of 31 and 40 years; 65.63% of the respondent had experience in rice processing of between 5 and 15 years. The adoption index of rice processing technologies indicated that the paddy cleaning and drying technique recorded 68.75% and 50.0% high adoption level respectively. Parboiling practices and de-stoning had recorded 58.75% and 71.88% medium adoption level respectively, while rice milling operation had recorded 61.25% low adoption. Tobit regression results indicated that gender was positively significant (P≤0.1); cost of the technology was negatively significant (P≤0.01); while the training (P≤0.01) and social capital (P≤0.05) were positively significant factors influencing the adoption of the rice processing technologies. The study recommends that capacity building (training) should be consistently conducted for updating the skills and knowledge of the rice processors. The rice processing technologies should be at low-cost within the financial reach of the processors, plus extension contact should be regular and timely by offering necessary advisory services and technical assistance so as to ensure continuous adoption of the technologies extended under the IFAD-VCDP intervention.